Pengaruh Promosi Media Digital dan Word Of Mouth Terhadap Keputusan Nasabah dalam Menggunakan BSI Mobile (Studi Kasus BSI KC Meulaboh Imam Bonjol) - Junaidi; Maskur (Teewan Journal Solutions, 2025)
Mobile banking application developed by Bank Syariah Indonesia to provide convenience for customers in accessing banking services. Although BSI Mobile is designed to facilitate banking transactions, there are still many customers who do not understand and are not very familiar with the BSI Mobile application. So many customers are still reluctant to switch from traditional banking methods to digital platforms. The purpose of this study was to determine the effect of digital media promotion and word of mouth on customer decisions to use BSI Mobile. The location of this research was conducted on Jalan Imam Bonjol, Johan Pahlawan District, West Aceh Regency. The objects in this study were digital media promotion, word of mouth and customer decisions at BSI KC Meulaboh Imam Bonjol. The results of the study showed that partially digital media promotion had a positive and significant effect on customer decisions in using the BSI Mobile application. Word of mouth had a positive and significant effect on customer decisions in using the BSI Mobile application. Simultaneously digital media promotion and word of mouth had a significant effect on customer decisions in using the BSI Mobile application at BSI KC Meulaboh Imam Bonjol.